Fe induction strategy for hollow porous N-doped carbon with superior performance in oxygen reduction. Issue 58 (28th June 2021) - Ye, Guanying; Wang, Siyuan; Liu, Suqin; He, Zhen; Wang, Jue
Abstract : A template-free Fe induction strategy is proposed for Co, Fe dual-metal N-codoped hollow porous carbon, which contributes to exposure of highly dispersed metal–N x sites, mass transport enhancement and therefore ORR catalytic performance elevation. Abstract : An Fe induction strategy is introduced to achieve template-free synthesis of Co, Fe dual-metal N-codoped hollow porous carbon from zeolitic imidazole frameworks, which is beneficial for the exposure of highly dispersed metal (M)–N x active sites and enhancement of mass transport, thereby exhibiting a superior electrocatalytic activity ( E 1/2, 0.86 VRHE ).